2019
DOI: 10.3390/a12020040
|View full text |Cite
|
Sign up to set email alerts
|

An INS-UWB Based Collision Avoidance System for AGV

Abstract: As a highly automated carrying vehicle, an automated guided vehicle (AGV) has been widely applied in various industrial areas. The collision avoidance of AGV is always a problem in factories. Current solutions such as inertial and laser guiding have low flexibility and high environmental requirements. An INS (inertial navigation system)-UWB (ultra-wide band) based AGV collision avoidance system is introduced to improve the safety and flexibility of AGV in factories. An electronic map of the factory is establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In recent years, intelligent and flexible manufacturing has motivated the development of autonomous mobile robots for workpiece and equipment handling and transportation [1,2], and in particular, automated guided vehicle (AGV) technology is widely studied and applied [3][4][5][6][7]. The omni-directional mobile AGV with Mecanum-wheeled robot platform, which has good driving force and easy control performance, can improve the utilization of workshop space and the efficiency of workshop transportation, and is very appropriate for transporting heavy goods in complex industrial environments [8,9]. The AGV that adopts a four-Mecanum-wheeled mobile robot platform with symmetrical structure is the most basic form and most widely used in industry [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, intelligent and flexible manufacturing has motivated the development of autonomous mobile robots for workpiece and equipment handling and transportation [1,2], and in particular, automated guided vehicle (AGV) technology is widely studied and applied [3][4][5][6][7]. The omni-directional mobile AGV with Mecanum-wheeled robot platform, which has good driving force and easy control performance, can improve the utilization of workshop space and the efficiency of workshop transportation, and is very appropriate for transporting heavy goods in complex industrial environments [8,9]. The AGV that adopts a four-Mecanum-wheeled mobile robot platform with symmetrical structure is the most basic form and most widely used in industry [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Udomsaksenee et al [35] proposed a global control method for Mecanum-wheeled vehicles with slip compensation.The latest research on cooperative transportation mainly focuses on path planning and navigation algorithms in working environments, and control methods in the cooperative transportation process. Research on the Mecanum-wheeled robot platform is mainly focused on single-Mecanum-wheeled robots [8,9,[36][37][38][39], while there is less research on the kinematic of a combination system and motion compensation of multiple-Mecanum-wheeled robot platforms. However, studying the kinematic and characteristics of the combined omnidirectional mobile system is the basis for studying the motion control, path planning, and navigation of the combination system.…”
mentioning
confidence: 99%
“…Reference [37] reported a position error of less than 0.5 m, although with a systematic shift, and they used five cameras to realize their method, which is impractical for forest surveys. Reference [44] used an extended Kalman filter (EKF) method that integrated inertial navigation system (INS) and UWB data. They tested their method in an indoor area of 10 × 10 m and found that the positioning error of UWB was between 10 and 30 cm and INS-UWB was less than 15 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Many proposed solutions rely on external infrastructures, especially for GPSrefused environments. Hamer and Andrea obtained global position with the assist of a ground anchor network consisting of UWB modules [8], so as some other similar research [20] [21] [22] [23] [24], and Xu et al expanded the anchor network by considering onboard UWB modules on UAVs [7]. For GPS-restricted environments, multi-UAVs coordination has been considered to improve GPS's robustness and accuracy [25] [26] [27].…”
Section: A Rl In Gps-denied Environmentmentioning
confidence: 99%